The Roles of Insurance on Economic Growth in Malaysia: An ARDL Approach - Nurhatiah Ahmad Chukari; Aufa Amanathul Kamila Lila Attahrir; Asmah Mohd Jaapar; Siti Masitah Elias; Ali Albada (Akademia Baru Publishing (M) Sdn Bhd, 2024)
Indexed by MyCite